THU0395 Influence of setting an upper limit of the mrss as an inclusion criterion in ssc clinical trials on the ratio of skin fibrosis progression vs. improvement – an analysis of the genisos cohort. (12th June 2018) - Mihai, C.; Dobrota, R.; Assassi, S.; Mayes, M.; Distler, O.; ,
Abstract : Background: Skin involvement is a main domain in the assessment of patients with systemic sclerosis (SSc), and the modified Rodnan skin score (mRSS) is a primary outcome measurement in SSc clinical trials. Recent studies on large SSc cohorts have shown that lowering the upper threshold of mRSS as a study inclusion criterion leads to cohort enrichment with patients with progressive skin disease. Limitations of these studies were lack of racial diversity and low proportion of patients with anti-RNA-Polymerase III (Pol3) antibodies. Objectives: As the Texas-based GENISOS is an ethnically diverse cohort and includes a large proportion of Pol3-positive patients, this study aimed to assess the effect of different mRSS cut-off values at baseline on progression of skin fibrosis after one year of follow-up. Methods: We extracted data from GENISOS for patients fulfilling the 1980 ACR criteria for SSc and the Le Roy criteria for diffuse cutaneous SSc, who had a mRSS ≥7 at inclusion and a follow-up visit with documented mRSS at 12±2 months. Progressors were defined as having an increase in mRSS >5 points and ≥25% from the baseline to 2nd visit, while regressors were defined as having a decrease in mRSS of >5 points and ≥25%. To identify the optimal cut-off of baseline mRSS that yields the highest sensitivity for progressive skin fibrosis, we developed ROC curves and logistic regression models with "progression" as outcome variable and a binary variable of baseline mRSS cut-off point as predictor. Results: We identified 152 patients (age and disease duration [median, Q1-Q3, years] 49.5, 40.2–57.3 and 2.2, 1.1–3.3 respectively, 22.4% males) who matched the inclusion criteria. The proportion of patients of African American ethnicity was 31/152 and 50/152 were Pol3-positive patients, both substantially higher than in European cohorts. After one year, 17 patients (11.2%) classified as progressors and 51 (33.6%) as regressors. Progressors were more frequently positive for anti-topoisomerase antibodies (37.5% vs. 15.3%, p=0.028), negative for anti-Pol3 antibodies (93.8% vs. 62.3%, p<0.012), had a shorter disease duration (median, Q1-Q3: 1.3, 0.5–2.2 vs. 2.4, 1.1–3.5 years, p<0.005) and lower mRSS (median, Q1-Q3: 21, 11–25 vs. 24, 16–31, p<0.012) than non-progressors. Sixteen of 17 progressors, but only 33 of 51 regressors had a baseline mRSS ≤27. The mRSS cut-off of ≤27 had the highest probability of progression (odds ratio 9.1, 95% confidence interval 1.2–70.9, p<0.035, area under the curve 0.652). Using this cut-off as an inclusion criterion (vs. no cut-off) would have included 94% of all progressors, but only 65% of all regressors and 67% of all patients. The figure 1 displays absolute numbers of progressors and regressors at 1 year for each mRSS cut-off. Conclusions: This analysis reconfirmed, in a population rich in patients of African American origin and with high prevalence of Pol3 antibodies, that setting a lower upper threshold of mRSS at study inclusion increases the proportion of progressors and reduces the absolute number of regressors. This confirms that this recruitment strategy should be used for clinical trial design in early diffuse SSc. Acknowledgements: The authors wish to thank all GENISOS investigators and patients. Disclosure of Interest: C. Mihai Grant/research support from: Actelion Pharmaceuticals Ltd, Abbvie, Speakers bureau: Roche, Geneva Romfarm, R. Dobrota Grant/research support from: Actelion Pharmaceuticals Ltd, Pfizer, S. Assassi Grant/research support from: U.S. National Institutes of Health-National Institute of Arthritis and Musculoskeletal and Skin Diseases, U.S. DOD Peer Reviewed Medical Research Program, Consultant for: Boehringer-Ingelheim, M. Mayes Grant/research support from: U.S. National Institutes of Health-National Institute of Arthritis and Musculoskeletal and Skin Diseases, U.S. DOD Peer Reviewed Medical Research Program, Consultant for: Boehringer-Ingelheim, Genentech, Astellas, Mitsubishi-Tanabe, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Mitsubishi Tanabe Pharma, Roche, Consultant for: Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa, UCB